Excellent benzocoumarin-based ratiometric two-photon fluorescent probe for H2O2 detection. Issue 1 (6th December 2018) - Hao, Xue-Li; Guo, Zi-Jing; Zhang, Chun; Ren, Ai-Min
Abstract : By analyzing the effect of benzene-fused position on a compound's optical properties, an excellent benzocoumarin-based two-photon fluorescent probe for H2 O2 detection was fabricated. Abstract : The level of hydrogen peroxide (H2 O2 ) plays an essential role in regulating biological processes. The in vivo or in vitro detection of H2 O2 in deep tissues by utilizing two-photon (TP) fluorescent probes can significantly alleviate the detection damage inflicted onto living organisms as well as facilitate high-resolution imaging when compared with one-photon (OP) fluorescent probes. However, few TP fluorescent probes possess both high fluorescence efficiency and easily distinguishable spectra for measuring H2 O2 . Therefore, an in-depth understanding of the relationship between the electronic structure and TP fluorescent properties and fabricating probes with excellent performance are still challenging. Consequently, we designed a series of benzocoumarin-based ratiometric TP fluorescent probes and corresponding product molecules for H2 O2 detection. Thereafter, we theoretically evaluated the TP recognition performance of these compounds and studied the relationship between their molecular structure and TP performance by means of time-dependent density functional theory and quadratic response theory. Moreover, we determined their spectral properties and fluorescence efficiencies. Fortunately, in this study, we were able to propose an excellent TP probeBC-3 and the corresponding product moleculeDCCA-3, which exhibit large TPA cross-sections in the NIR region (3420 GM/988 nm; 316 GM/939 nm) and large Stokes (116 nm; 60 nm) and emission (225 nm) shifts. Therefore, this probe enables the simultaneous NIR and TP imaging of H2 O2, which is a unique ability and has never been previously reported. Moreover, we comprehensively investigated the effect of the benzene-fused position in the coumarin backbone on the transition dipole moment and nonradiative decay channels, explaining the fluorescence near-quenching mechanism of benzo[ f ]coumarin derivativeDCCA-4 for the first time.